Fire patterns in north-eastern Argentina: influences of climate and land use/cover - Di Bella, Carlos Marcelo (2011)
Fires are one of the most frequent disturbances on terrestrial ecosystems, thus making their understanding and prediction crucial for their management. While the fuels condition are linked to well-known environmental factors, the ignition triggering agents are less understood and may display a more stochastic behaviour. We studied the regional relationship between the fire density and frequency, climate and land use/cover in the north-east region of Argentina using Moderate Resolution Imaging Spectroradiometer (MODIS) hotspots data, daily weather reports and land use/cover data at national level. The pre-fire water availability index showed a significantly negative relationship with hotspot densities (r 2 = 0.51, p < 0.01). The uncultivated land coverage, mainly represented by natural grasslands, was positively associated with the fire density (for Entre Rios, r 2 = 0.74, p < 0.0001 and for Corrientes, r 2 = 0.67, p < 0.0001). The results highlight the potential of remote sensing for fire monitoring in this region and its value in urgently needed policies for fire control and management.